The Effect of an Educational Program Using the Cooperative Learning Method on Learning the Setting Skill in Volleyball - Abeer Mohammed Nouri Ali, (Eximia, 2025)
This study aims to examine the effect of the cooperative learning method compared to the traditional method in learning the setting skill in volleyball among students of the College of Physical Education and Sports Sciences at the University of Babylon. The research employed an experimental design with a sample divided into two groups: an experimental group that learned using the cooperative learning method and a control group that learned using the traditional method. After implementing the educational program, the results showed a significant and statistically meaningful superiority in favor of the group that used cooperative learning in improving the technical performance of the skill. This is attributed to the students' interaction and increased opportunities for innovation and effective collaboration among them, which positively impacted the acquisition of the complex motor skill. Therefore, it is recommended to adopt the cooperative learning method as an effective strategy for developing sports skills in educational settings.